A binderless wc-based cemented carbide and a method for producing the same

CN117923904BActive Publication Date: 2026-10-30NANCHANG HANGKONG UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410115597.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-26
Publication Date
2026-10-30
Estimated Expiration
2044-01-26

AI Technical Summary

Technical Problem

[0008]因此,现有技术中还没有公开一种原位生长Al2O3柱状晶和ZrO2(3Y)协同强韧化的无粘结相WC基硬质合金及其制备方法,遂有了本发明

Benefits of technology

[0024](1)采用快速热压烧结技术,无需预压和烧结助剂,烧结速率快,合金致密度好,无需昂贵的脉冲电源,相比放电等离子烧结设备投资少,烧结温度低。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117923904B_ABST
    Figure CN117923904B_ABST
Patent Text Reader

Abstract

The application discloses a binderless WC-based hard alloy and a preparation method thereof, wherein the preparation method comprises the following steps: S1, WC powder, Al2O3 powder and ZrO2(3Y) powder are added into a hard alloy ball mill jar, anhydrous ethanol is used as a ball mill medium, the hard alloy ball mill jar containing the mixed powder is placed into a planetary ball mill for wet milling, and a slurry with uniform mixing is obtained; S2, the hard alloy ball mill jar containing the slurry is taken out and placed into a vacuum drying box for drying, and the slurry is sieved after drying; and S3, the powder is placed into a rapid hot-pressing sintering furnace, an inert atmosphere is used for protection, and the embryo is kept at a preset temperature after rapid hot-pressing sintering, so that a binderless WC-based hard alloy material with in-situ growth Al2O3 columnar crystals and ZrO2(3Y) synergistic toughening is obtained; the material is added with the in-situ growth Al2O3 columnar crystals, the hardness of the alloy is enhanced, and the fracture toughness and the bending strength of the alloy are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of alloy materials, specifically to a binderless WC-based cemented carbide and its preparation method. Background Technology

[0002] Binderless tungsten carbide (BTC) is a research hotspot in the field of WC-based cemented carbide. BTC possesses a high melting point and excellent corrosion resistance, making it more suitable for harsh environments such as high-temperature and highly corrosive conditions compared to WC-based cemented carbides using metals like WC-Co as binders. While Co-based binders can improve the toughness of cemented carbides, they reduce the alloy's hardness, oxidation resistance, and corrosion resistance. Therefore, binderless tungsten carbides possess superior properties not found in traditional cemented carbides and are widely used in cutting tools, mining tools, impact tools, drill bits, and abrasive tools, improving tool life and efficiency. Furthermore, it can be used in demanding fields such as mold making and aerospace. Binderless tungsten carbide is one of the important materials in modern industrial machining.

[0003] Adding oxide ceramics (Al2O3, MgO, and ZrO2, etc.) significantly improves their toughness. If the WC grains can be further refined, WC-Me ceramics can be expected to achieve similar results. x O y The system will possess high strength and toughness, making it suitable for use as a cutting tool. ZrO2, as a high-temperature resistant oxide, can improve the sintering performance of binderless WC-based cemented carbides and possesses a phase transformation toughening mechanism, enhancing the strength and toughness of the alloy. Further addition of micron-sized Al2O3 powder allows for in-situ growth of columnar crystals through sintering, promoting the increase in strength and hardness of the binderless WC-based cemented carbides, increasing crack propagation ability, and achieving the goal of toughening. However, the densification temperature of binderless cemented carbides is high, making it difficult to densify using conventional sintering methods. Rapid hot pressing sintering technology, with its fast heating and cooling rates and low sintering temperatures, is the most powerful tool for sintering advanced materials such as special ceramic materials.

[0004] A search revealed that Chinese patent document CN107099720A discloses a cemented carbide tool material for aluminum alloy machining and its preparation method. The material is made from a composition comprising Co, WC, and ZrO2, and also includes Al2O3. The ZrO2 particle size is 5–50 nm, and the Al2O3 particle size is 5–55 nm. In the composition, the weight percentage of ZrO2 is 0.2–1.5%, and the weight percentage of Al2O3 is 0.1–1%. The preparation method is as follows: (1) ZrO2 and Al2O3 are mixed and pretreated; (2) the mixture is prepared and shaped; (3) vacuum sintering; and (4) low-pressure sintering to obtain the cemented carbide tool material. This invention uses nano-zirconia and nano-alumina as grain size inhibitors to reduce the grain size of the WC hard phase, improve the material hardness, and enhance the cutting wear resistance of the cutting tool. Furthermore, due to the relatively low price of zirconia and alumina, the production cost is significantly reduced.

[0005] Chinese patent document CN105522137A discloses a metal-ceramic composite and its preparation method. The metal-ceramic composite includes a ceramic matrix and a metal component. The surface of the ceramic matrix has grooves, and the metal component fills the grooves. The metal component includes a zirconium-based alloy and a reinforcing material located within the zirconium-based alloy. The reinforcing material is selected from one or more of W, Mo, Ni, Cr, stainless steel, WC, TiC, SiC, ZrC, ZrO2, BN, Si3N4, TiN, and Al2O3. The surface luminance L value of the metal component in the LAB colorimetric system is 36.92-44.07. The metal-ceramic composite provided by this invention has high surface hardness of the metal component, strong bonding force with the ceramic matrix, and good appearance performance.

[0006] Analysis revealed that the cemented carbide cutting tool material for aluminum alloy machining disclosed in CN107099720A uses Co as the binder phase, WC as the main tool material, and nano-ZrO2 and nano-Al2O3 as grain inhibitors to suppress WC grain growth, thereby increasing the material's hardness and improving the cutting and wear resistance of the cutting tool. Without Co as the binder phase, its performance would be unpredictable. For example, the amount of Al2O3 used was controlled during the preparation process to ensure good wettability between Al2O3 and the binder phase Co.

[0007] The metal-ceramic composite disclosed in CN105522137A includes a ceramic matrix and a metal component. The metal component comprises a zirconium-based alloy and a reinforcing material located within the zirconium-based alloy. The reinforcing material is granular with a particle size D50 of 0.1-100 μm and is uniformly dispersed within the zirconium-based alloy. The performance requirement of the reinforcing material depends on effective bonding with the zirconium-based alloy, preferably using W and Mo. This is because the melting points of the reinforcing materials used (e.g., W's melting point is 3410℃, and Mo's melting point is 2610℃) are higher than those of conventional zirconium-based alloys, which facilitates effective bonding between the zirconium-based alloy and the reinforcing material during the preparation process.

[0008] Therefore, the prior art has not disclosed a binderless WC-based cemented carbide with in-situ growth of Al2O3 columnar crystals and synergistic strengthening of ZrO2(3Y) and its preparation method, hence this invention. Summary of the Invention

[0009] In view of this, in order to solve the above-mentioned technical problems, the purpose of this invention is to propose a binderless WC-based cemented carbide and its preparation method. A binderless WC-based cemented carbide material with in-situ grown Al2O3 columnar crystals and ZrO2(3Y) synergistic strengthening is prepared, which improves mechanical properties and solves some of the defects of traditional cemented carbide.

[0010] The technical solution adopted is as follows:

[0011] The present invention discloses a method for preparing a binderless WC-based cemented carbide, comprising the following steps:

[0012] S1. Add WC powder, Al2O3 powder and ZrO2(3Y) powder into a cemented carbide ball milling jar, use anhydrous ethanol as the ball milling medium, place the cemented carbide ball milling jar containing the mixed powder into a planetary ball mill for wet ball milling, and obtain a uniformly mixed slurry.

[0013] S2. Remove the cemented carbide ball mill jar containing the slurry, place it in a vacuum drying oven to dry, and then sieve it after drying;

[0014] S3. Place the powder in a rapid hot pressing sintering furnace, use an inert atmosphere for protection, and rapidly hot press sinter the green body to reach the preset temperature and then hold it at that temperature to obtain an in-situ grown Al2O3 columnar crystal and ZrO2(3Y) synergistically strengthened unbound phase WC-based cemented carbide material.

[0015] Furthermore, in S1, the mass fraction of Al2O3 powder in the cemented carbide ball mill jar is 2-10 wt%, the mass fraction of ZrO2(3Y) powder is 6-12 wt%, and the mass fraction of WC powder is 78-92 wt%.

[0016] Furthermore, in S1, the ball milling time is 30-32 hours and the rotation speed is 150-200 r / min.

[0017] Furthermore, in S2, the drying time is 24-26 hours and the drying temperature is 80-90℃.

[0018] Furthermore, in S2, it passes through a 200-250 mesh sieve.

[0019] Furthermore, in S3, the sintering current is direct current; the sintering pressure is 30-45 MPa; the sintering temperature is 1450-1650℃; the holding time is 3-10 min; the heating rate is 50-130℃ / min; and the sintering atmosphere is argon gas introduced into the furnace cavity after the furnace cavity is evacuated as a protective gas to maintain the vacuum degree in the furnace at 10±0.2 Pa.

[0020] The present invention discloses a binderless WC-based cemented carbide, which is prepared by the preparation method described above.

[0021] In the technical solution of this invention, the raw material ZrO2(3Y) refers to the zirconium oxide material containing 3% molar percentage of the stabilizer yttrium oxide. It has a tetragonal crystal form and the raw material is commercially available.

[0022] This invention employs a rapid hot-pressing sintering method and utilizes Al2O3 and ZrO2(3Y) to strengthen the mechanical properties of WC-based cemented carbide materials. With WC as the matrix, Al2O3 as the auxiliary strengthening phase, and ZrO2(3Y) as a sintering aid, strengthening phase, and induction agent, it significantly reduces the sintering temperature, refines the grain size, and promotes in-situ growth of Al2O3 columnar crystals. This achieves the goal of synergistic strengthening and toughening of WC-based cemented carbide through the in-situ growth of Al2O3 columnar crystals and ZrO2(3Y).

[0023] Compared with the prior art, the outstanding advantages of the present invention are:

[0024] (1) The rapid hot pressing sintering technology is adopted, which does not require pre-pressing and sintering aids. The sintering rate is fast, the alloy density is good, and there is no need for expensive pulse power supply. Compared with the discharge plasma sintering equipment, the investment is less and the sintering temperature is lower.

[0025] (2) By utilizing the toughening mechanism of ZrO2(3Y) phase transformation, the strength and toughness of the unbound WC-based cemented carbide are improved. The raw materials are low in cost and easy to obtain. This not only significantly reduces the sintering temperature, but also effectively improves the density of the alloy.

[0026] (3) Adding Al2O3 to grow columnar crystals in situ enhances the hardness of the alloy, improves its fracture toughness and bending strength, resulting in high hardness, fracture toughness and bending strength. Attached Figure Description

[0027] The accompanying drawings, which are provided to further illustrate the invention and constitute a part of this invention, are illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention.

[0028] Figure 1 XRD pattern of WC-based cemented carbide material with synergistic toughening by Al2O3 and ZrO2(3Y).

[0029] Figure 2 A magnified SEM image of a WC-based cemented carbide material synergistically strengthened by Al2O3 and ZrO2(3Y).

[0030] Figure 3 This is a magnified SEM image of another WC-based cemented carbide material synergistically strengthened by Al2O3 and ZrO2(3Y). Detailed Implementation

[0031] The embodiments of the present invention will be described in detail below with reference to the accompanying drawings and examples, so that the process of how the present invention uses technical means to solve technical problems and achieve technical effects can be fully understood and implemented accordingly. However, the uses and purposes of these exemplary embodiments are only for illustrating the present invention and do not constitute any limitation on the actual protection scope of the present invention, nor are they intended to limit the protection scope of the present invention to this.

[0032] Example 1

[0033] A method for preparing WC-based cemented carbide with synergistic strengthening and toughening of mechanical properties by in-situ growth of Al2O3 columnar crystals and ZrO2(3Y) includes the following steps:

[0034] (1) 68.8g of WC powder (particle size 0.8μm, purity >99.9%), 8g of ZrO2(3Y) powder (particle size 30nm, purity >99.9%) and 3.2g of Al2O3 (particle size 1μm, purity >99.9%) were poured into a cemented carbide ball mill jar, and 15ml of anhydrous ethanol was added as the ball milling medium. The cemented carbide ball mill jar containing the mixed powder was placed in a planetary ball mill for wet milling for 30h at a speed of 150r / min to obtain a uniformly mixed slurry.

[0035] (2) Place the cemented carbide ball mill jar containing the mixed slurry into a vacuum drying oven for drying for 24 hours at a temperature of 80°C.

[0036] (3) Pass the dried powder through a 200-mesh sieve to form a composite powder with uniform and fine particles.

[0037] (4) Place the composite powder in an inner diameter of In the cylindrical graphite mold, the composite powder is separated from the mold and the upper and lower graphite rods by graphite paper to prevent the powder from sticking to the mold during sintering and to facilitate demolding. A layer of asbestos felt is wrapped around the concave mold to prevent heat loss. The temperature in the furnace is measured using an infrared thermometer.

[0038] (5) The graphite mold containing the composite powder was placed in a rapid hot pressing sintering furnace for sintering. The sintering process was as follows: sintering pressure 40MPa, sintering temperature 1600℃, holding time 5min; heating rate 80℃ / min; sintering atmosphere was argon gas introduced into the furnace after the furnace cavity was evacuated to a vacuum, and the vacuum degree in the furnace was maintained at 10±0.2Pa; WC-based cemented carbide material with Al2O3 and ZrO2(3Y) synergistic strengthening and toughening was obtained.

[0039] The Al2O3 and ZrO2(3Y) synergistically reinforced and toughened WC-based cemented carbide material obtained through the above method was measured to have a relative density of 99.9%, a Vickers hardness of 2300 HV, and a fracture toughness of 12.3 MPa·m. 1 / 2 Its flexural strength is 1700MPa.

[0040] See also Figure 1 As shown in the XRD pattern, it can be seen that a WC-based cemented carbide material with Al2O3 and ZrO2(3Y) synergistic strengthening was formed.

[0041] See Figure 2 and Figure 3 As shown, the prepared WC-based cemented carbide material has in-situ grown Al2O3 columnar crystals.

[0042] Example 2

[0043] A method for preparing WC-based cemented carbide with synergistic strengthening and toughening of mechanical properties by in-situ growth of Al2O3 columnar crystals and ZrO2(3Y) includes the following steps:

[0044] (1) 65.6g of WC powder (particle size 0.8μm, purity >99.9%), 8g of ZrO2(3Y) powder (particle size 30nm, purity >99.9%) and 6.4g of Al2O3 (particle size 1μm, purity >99.9%) were poured into a cemented carbide ball mill jar, and 15ml of anhydrous ethanol was added as the ball milling medium. The cemented carbide ball mill jar containing the mixed powder was placed in a planetary ball mill for wet milling for 30h at a speed of 150r / min to obtain a uniformly mixed slurry.

[0045] (2) to (4) are the same as steps (2) to (4) in Example 1;

[0046] (5) The graphite mold containing the composite powder was placed in a rapid hot pressing sintering furnace for sintering. The sintering process was as follows: sintering pressure 40MPa, sintering temperature 1600℃, holding time 5min; heating rate 80℃ / min; sintering atmosphere was argon gas introduced into the furnace after the furnace cavity was evacuated to a vacuum, and the vacuum degree in the furnace was maintained at 10±0.2Pa; WC-based cemented carbide material with Al2O3 and ZrO2(3Y) synergistic strengthening and toughening was obtained.

[0047] The Al2O3 and ZrO2(3Y) synergistically reinforced and toughened WC-based cemented carbide material obtained through the above method was measured to have a relative density of 99.7%, a Vickers hardness of 2249 HV, and a fracture toughness of 12.0 MPa·m. 1 / 2 Its flexural strength is 1655 MPa.

[0048] Example 3

[0049] A method for preparing WC-based cemented carbide with synergistic strengthening and toughening of mechanical properties by in-situ growth of Al2O3 columnar crystals and ZrO2(3Y) includes the following steps:

[0050] (1) to (4) are the same as steps (1) to (4) in Example 1;

[0051] (5) The graphite mold containing the composite powder was placed in a rapid hot pressing sintering furnace for sintering. The sintering process was as follows: sintering pressure 40MPa, sintering temperature 1550℃, holding time 5min; heating rate 80℃ / min; sintering atmosphere was argon gas introduced into the furnace after the furnace cavity was evacuated to a vacuum, and the vacuum degree in the furnace was maintained at 10±0.2Pa; WC-based cemented carbide material with Al2O3 and ZrO2(3Y) synergistic strengthening and toughening was obtained.

[0052] The Al2O3 and ZrO2(3Y) synergistically strengthened and toughened WC-based cemented carbide material obtained through the above method was measured to have a relative density of 99.6%, a Vickers hardness of 2224 HV, and a fracture toughness of 11.7 MPa·m. 1 / 2 Its flexural strength is 1620 MPa.

[0053] The detailed descriptions listed above are merely specific illustrations of feasible embodiments of the present invention and are not intended to limit the scope of protection of the present invention. All equivalent embodiments or modifications made without departing from the spirit of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a binderless WC-based cemented carbide, characterized in that, Includes the following steps: S1. Add WC powder, Al2O3 powder and 3Y ZrO2 powder to a cemented carbide ball milling jar, use anhydrous ethanol as the ball milling medium, place the cemented carbide ball milling jar containing the mixed powder into a planetary ball mill for wet milling, and obtain a uniformly mixed slurry. S2. Remove the cemented carbide ball mill jar containing the slurry, place it in a vacuum drying oven to dry, and then sieve it after drying; S3. The powder is placed in a rapid hot-pressing sintering furnace and protected with an inert atmosphere. Rapid hot-pressing sintering is performed to allow the green body to reach the preset temperature and then hold it at that temperature to obtain an in-situ grown Al2O3 columnar crystal and 3Y ZrO2 synergistically strengthened and toughened unbound phase WC-based cemented carbide material. The sintering current is direct current; the sintering pressure is 30-45 MPa; the sintering temperature is 1450-1650℃; the holding time is 3-10 min; the heating rate is 50-130℃ / min; the sintering atmosphere is argon gas introduced into the furnace after the furnace cavity is evacuated to a vacuum to maintain a vacuum degree of 10±0.2 Pa.

2. The method for preparing the binderless WC-based cemented carbide according to claim 1, characterized in that, In S1, the mass fraction of Al2O3 powder in the cemented carbide ball mill jar is 2-10 wt%, the mass fraction of 3Y ZrO2 powder is 6-12 wt%, and the mass fraction of WC powder is 78-92 wt%.

3. The method for preparing the binderless WC-based cemented carbide according to claim 1, characterized in that, In S1, the wet grinding time is 30-32 hours and the rotation speed is 150-200 r / min.

4. The method for preparing a binderless WC-based cemented carbide according to claim 1, characterized in that, In S2, the drying time is 24-26 hours and the drying temperature is 80-90℃.

5. The method for preparing the binderless WC-based cemented carbide according to claim 1, characterized in that, In S2, it passes through a 200-250 mesh sieve.

6. A binderless WC-based cemented carbide, characterized in that, It is prepared by any of the preparation methods described in claims 1-5.

Citation Information

Patent Citations

  • Metal ceramic composite and preparation method thereof

    CN105522137A

  • Hard alloy cutter material used for processing aluminum alloy and preparing method thereof

    CN107099720A

  • Unbonded-phase tungsten carbide composite material and preparation method thereof

    CN105272260A

  • Zirconia composite alumina ceramic sintered body as well as preparation method and application thereof

    CN112142450A